In vitro analysis of shear bond strength and adhesive remnant index comparing light curing and self-curing composites - Murilo Gaby Neves; Gustavo Antônio Martins Brandão; Haroldo Amorim de Almeida; Ana Maria Martins Brandão; Dário Ribeiro de Azevedo (Dental Press Editora, 2013)
OBJECTIVE: To evaluate, in vitro, the shear bond strength of self-curing (ConciseTM - 3M and Alpha Plast - DFL) and light-curing composites (TransbondTM XT - 3M and Natural Ortho - DFL) used in orthodontics bonding, associated to Morelli metal brackets, with further analysis of adhesive remnant index (ARI) and enamel condition in scanning electron microscopy (SEM). METHODS: Forty human premolars, just extracted and stored in physiologic solution 0.9 % were used. Randomly, these samples were divided in four groups: G1 group, the brackets were bonded with ConciseTM - 3M composite; in G2 group, Alpha Plast - DFL composite was used; in G3 group, TransbondTM XT - 3M was used; in G4 group, Natural Ortho - DFL composite was used. These groups were submitted to shear strength tests in universal testing machine, at 0.5 mm per minute speed. RESULTS: Statistical difference between G3 and G4 groups was recorded, as G4 showing higher strength resistance than G3. In the other hand, there were no statistical differences between G1, G2 and G3 and G1, G2 and G4 groups. ARI analysis showed that there was no statistical difference between the groups, and low scores were recorded among then. The scanning electron microscopy (SEM) analysis revealed the debonding spots and the enamel surface integrity. CONCLUSIONS: Shear bond strength was satisfactory and similar between the composites, however Natural Ortho - DFL revealed best comparing to TransbondTM XT - 3M.